Cervezas Amargas: un problema de orientación espacial resuelto - Medina, Juan Pablo (Pontificia Universidad Católica del Perú, 2013)
Determination of the stereochemistry of organic compounds has been a problem that the scientific community has been giving solution to over the years. Different methods have emerged, such as X-ray Diffraction or different types of Nuclear Magnetic Resonance (NMR). However, it just has been discovered that the method used in the determination of the absolute configuration of the α-acids derived from hops used in the manufacture of bitter beers, was not the appropriate.

La determinación de la estereoquímica en los compuestos orgánicos ha sido un problema que la comunidad científica ha ido dando solución a lo largo de los años. Diferentes métodos han surgido, como la difracción de rayos X o los distintos tipos de Resonancia Magnética (RMN). Sin embargo, se acaba de descubrir que el método utilizado hasta ahora en la determinación de la configuración absoluta de los α-ácidos, que provienen del lúpulo utilizado en la elaboración de las cervezas bitter, parece que no era el correcto.
Bitter beers: a spatial orientation problem solved
Keywords: Cerveza; Quiralidad; Alfa-ácidos; Lúpulo; https://purl.org/pe-repo/ocde/ford#1.04.00